Emergency Department Specific Antimicrobial Stewardship Intervention Reduces Antibiotic Duration and Selection for Discharged Adult and Pediatric Patients with Skin and Soft-tissue infections. (4th October 2017) - Trajano, Renee; Ondak, Susan; Tancredi, Dan; Wiedeman, Jean; Cohen, Stuart H; Miller, Loren; Anderson, Chance; May, Larissa
Abstract: Background: Skin and soft-tissue infections (SSTI) account for 2.4 million annual U.S. emergency department (ED) visits. A majority of physicians give empiric antibiotic treatment that is non-compliant with guidelines, leading to potential patient harm and fueling the emergence of antibiotic resistance. The ED is a deserving focus of antimicrobial stewardship yet interventions have not been well studied in this setting. Methods: Quasi-experimental study of a multifaceted antimicrobial stewardship intervention at an academic ED in a setting of high prevalence of clindamycin resistance among S. aureus. Our intervention included educational presentations by a physician champion, implementation of an electronic order set based on 2014 IDSA guidelines, dissemination of an ED specific S. aureus wound isolate antibiogram, monthly departmental peer-comparisons, and bimonthly, confidential, individual audit and feedback. Visits with ICD-10 codes for cutaneous abscess or other SSTI for patients discharged to home from the ED for consented providers were included for analysis. Primary endpoint of antibiotic selection and treatment duration was assessed during the pre-intervention and intervention periods using contingency tables for categorical outcome and a linear regression model for clustered survey data for comparing mean durations. Results: Seventy-four consented providers' data were included, accounting for 310 patient visits over the baseline (Oct 15-Mar 16) and 315 visits over the intervention period (Oct 16-Mar 17). Mean antibiotic duration decreased from 9.5 to 6.5 days, a difference (95% CI adjusted for provider cluster effects) of -3.0 (-0.6, -5.3) days. Among patients discharged with a diagnosis of abscess, the use of >2 antibiotics declined from 12% (15/125) in the baseline to 4% (4/110) in the intervention period. The relative frequency of clindamycin use decreased from 59% to 23%. Among patients discharged with a diagnosis of cellulitis, cephalexin use increased from 22% to 42%, with clindamycin use declining from 58% to 28%. Conclusion: Our ED specific antibiotic stewardship program successfully reduced antibiotic duration and improved guideline adherence in discharged patients with SSTI. Similar implementation strategies should be assessed in a wider variety of settings. Disclosures: All authors: No reported disclosures.